A Theological Perspective on the LGBTQ+ Phenomenon and the Importance of Providing Education to Church Congregations - Banarto, Kris; Silaban, Guntur Hamonangan Sahat (Jurnal Indonesia Sosial Sains, 2025)
LGBTQ+ has become a phenomenon and polemic, even with a fairly massive campaign they claim LGBTQ+ as a lifestyle. In the past, this activity was carried out in secret and now it is done openly. The significant development from year to year by this community cannot be separated from the support of the state that legalizes same-sex marriage, until now there have been at least 38 countries. (Liputan6.com, January 24, 2025). Churches in 38 countries have partly legalized same-sex marriage and can perform marriage blessings by priests. With the phenomenon of LGBTQ+ behavior, this article presents a theological view of the LGBTQ+ phenomenon. To anticipate the congregation from the influence of this group, the church needs to be present to provide education about LGBTQ+ biblically so that the congregation has a strong faith and is not influenced by this deviant movement. The author understands that there are already many articles that discuss LGBTQ+ theologically, but those that discuss education for the congregation specifically do not exist or are still limited. The research method used is a literature study of biblical exegesis, especially regarding Imago Dei and Creation Theology and the need for education, supplemented by the opinions of theologians, commentaries, journal studies, books, and other literature. The author found that LGBTQ+ behavior is contrary to the Bible, so it is important to have an educational pattern for the congregation with comprehensive materials and methods adjusted to the age level of the congregation so that education is effective.